Enhancement of Photonic Band Gap in One Dimensional Plasma-Dielectric Ternary Photonic Crystal - Pandey, Girijesh Narayan; Kumar, Narendra; Kumar, Asish; Thapa, Khem B.; Kaliramna, Sonu (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
We theoretically design a multilayer structure of hyperbolic meta-material based on plasma photonic crystal which is composed of traditional dielectric and plasma materials. The reflection, transmission and absorption spectra of the multilayer ternary periodic structure at normal incidence have been investigated using transfer matrix method. We have analyzed that the reflection, the transmission and the absorption are highly affected with the variable parameters of optical constants. Such a structure shows a similar good absorptive nature up to normalized frequency 2.25, while above this frequency, it exhibits multiple broadband electromagnetic wave tunneling. The calculated results reveal an innovative idea in designing some optical devices using such hyperbolic meta-material based photonic crystal with wideband tunneling.